Digital Humanities Looking at the World - Araújo, Sílvia,Aguiar, Micaela,Ermakova, Liana (Springer Nature Switzerland, Imprint: Palgrave Macmillan, 2024)
Zusammenfassung: This edited volume explores how digital humanities can address critical societal challenges in social media, health, education, archives, heritage, and the arts. It features contributions from leading scholars and practitioners in various fields, offering a comprehensive overview of the role of digital humanities in addressing pressing social and economic issues. Designed for scholars, researchers, and practitioners in digital humanities, social sciences, arts, and cultural studies, the book highlights the potential of digital technologies to tackle today's most urgent problems, making it a valuable resource for those interested in harnessing digital innovation for societal benefit. Sílvia Araújo is an Assistant Professor at the University of Minho, Portugal, specializing in corpus linguistics, language technologies, and digital humanities. She leads FCT-funded projects (Perfide, PortLinguE) and IDEA-UMinho initiatives. Sílvia directs the Master's Degree in Digital Humanities, heads the Digital Humanities Research Group, and oversees the journal H2D. She contributes to journals like Myriades, PSIQUE, and Polissema and organizes the annual techLING conference on language technology. Micaela Aguiar is a post-doctoral researcher on the project PortLinguE, Multilingual Portal for Specialized Languages: mining open data for cross-language information retrieval, at the University of Minho, Portugal. She recently completed her Ph.D in linguistics, in the field of Discourse Analysis. Micaela Aguiar’s research interest lies in digital humanities, corpus linguistics and NLP, which she hopes to explore further in her future work. Liana Ermakova, an associate professor at the University of Western Brittany since 2017, specializes in information retrieval, natural language processing, and AI. Her work encompasses evaluation metrics, information analysis, multi-document summarization, text simplification (SimpleText), and scientometrics. She leads the JOKER project (2021-2022), building a wordplay corpus. She's also active in organizing conferences, workshops, and AI competitions
10.1007/978-3-031-48941-9
Keywords: (lcsh)Linguistics–Methodology.; (lcsh)Digital humanities.; (lcsh)Multilingualism.; Research Methods in Language and Linguistics.; Digital Humanities.; Multilingualism.